Conceptual Nuclear Design of a 20 MW Multipurpose Research Reactor - Nguyen , Nhi Dien; Huynh , Ton Nghiem; Le , Vinh Vinh; Vo Doan , Hai Dang; Seo , Chulgyo; Park , Cheol; Kim , Hak Sung (Nuclear Science and Technology, 2014)
This paper presents some of studied results of a pre-feasibility project on a new research reactor for Vietnam. In this work, two conceptual nuclear designs of 20 MW multi-purpose research reactor have been done. The reference reactor is the light water cooled and heavy water reflected open-tank-in-pool type reactor. The reactor model is based on the experiences from the operation and utilization of the HANARO. Two fuel types, rod and flat plate, with dispersed U3Si2-Al fuel meat are used in this study for comparison purpose. Analyses for the nuclear design parameters such as the neutron flux, power distribution, reactivity coefficients, control rod worth, etc. have been done and the equilibrium cores have been established to meet the requirements of nuclear safety and performance.